Association of soybean-based food with the prevalence of anaemia among reproductive-aged men and women in rural Central Java, Indonesia. Issue 12 (27th December 2022) - Lowe, Callum; Sarma, Haribondhu; Kelly, Matthew; Kurscheid, Johanna; Laksono, Budi; Amaral, Salvador; Stewart, Donald; Gray, Darren
Abstract: Objective: To assess the association between soybean consumption and anaemic status in Central Java, Indonesia. Design: As part of an overarching sanitation improvement intervention in Central Java, Indonesia, we conducted a cross-sectional study in four rural villages. The study consisted of a 24-h food recall, anthropometric measurements, blood Hb measurement and stool sampling to test for soil-transmitted helminth (STH) infection status. A binary logistic regression model was fitted to test the association between soybean consumption and anaemic status after adjusting for socio-demographic factors, STH infection, dietary diversity and anthropometric status. Setting: This study took place in four rural villages of Wonosobo regency, Central Java, Indonesia. Participants: Participants were rural villagers aged between 15 and 49 years. Results: A total sample size of 763 was attained, of which 231 were anaemic. The prevalence of anaemia was 30·2 % among men and women of reproductive age, and highest among young males. Consumption of soybean was high (79·8 %). After adjusting for covariates, the protective association between soybean consumption and anaemia was statistically significant (AOR = 0·53, 95 % CI = 0·30, 0·95, P < 0·05). There was a positive association with anaemia among underweight (AOR = 2·75, 95 % CI = 1·13, 6·69, P < 0·05) and those with high diet diversity (AOR = 1·40, 95 % CI = 1·00, 1·97, P < 0·05). Conclusions: Our results were consistent with studies from other countries finding a protective association between soybean consumption and anaemia. This association appeared stronger for tofu than for tempeh. The prevalence of anaemia in rural Central Java is relatively consistent with nation-wide statistics indicating that interventions targeting anaemia are still largely required.